Cohort of Patients Referred for Brugada Syndrome Investigation in an Electrophysiology Service - 19-Year Registry - Warpechowski Neto,Stefan (2018)
Abstract Background: Brugada syndrome (SBr) is an arrhythmic condition characterized by ST-T segment abnormalities in the right precordial leads associated with a high risk of ventricular arrhythmias and sudden death. Local data regarding the clinical characteristics of patients with a typical electrocardiographic (ECG) pattern undergoing electrophysiological study are scarce. Objective: To evaluate patients with an ECG pattern suggestive of SBr referred for electrophysiological evaluation in a specialized center. Methods: Cohort study of patients referred for electrophysiological study because of an ECG pattern compatible with SBr between January 1998 and March 2017. Results: Of the 5506 procedures, 35 (0.64%) were for SBr investigation, 25 of which (71.42%) were performed in men. The mean age was 43.89 ± 13.1 years. The ECG patterns were as follows: type I, 22 (62.85%); type II, 12 (34.30%); and type III, 1 (2.85%). Twenty-three patients (65.7%) were asymptomatic, 6 (17.14%) had palpitations, 5 (14.3%) had syncope, and 3 (8.6%) had a family history of sudden death. Electrophysiological study induced ventricular tachyarrhythmias in 16 cases (45.7%), the mean ventricular refractory period being 228 ± 36 ms. Ajmaline / procainamide was used in 11 cases (31.4%), changing the ECG pattern to type I in 7 (63.6%). Sixteen cases (45.7%) received an implantable cardioverter defibrillator (ICD). In a mean 5-year follow-up, 1 of the 16 patients (6.25%) with ICD had appropriate therapy for ventricular fibrillation. There was no death. Other arrhythmias occurred in 4 (11.4%) cases. Conclusions: Most patients are men, and a type I ECG pattern is the main indication for electrophysiological study. Class IA drugs have a high ECG conversion rate. The ICD event rate was 6%. (Arq Bras Cardiol. 2018; [online].ahead print, PP.0-0)